Treatment of proximal patellar tendon rupture with custom-made anchor-like plate and suture: cases report and literature review - Qi, Hongfei; Li, Zhong; Ma, Teng; Ren, Cheng; Xu, Yibo; Huang, Qiang; Zhang, Kun; Li, Ming (Frontiers in Surgery, 2023)
We reported 2 cases of patellar tendon rupture at the lower pole of the patella. For patellar tendon rupture, simple suture fixation has been proved to be inadequate in strength. Our center uses custom-made anchor-like plate and suture to treat proximal patellar fracture. The fixation strength is reliable, no additional bone tunnel is required, and the fixation of the lower patellar fracture can be achieved at the same time. After the operation, the patient starts functional exercise of the knee joint at an early stage, The function of the knee joint of the patient recovered well after 1 year, without other complications.